The Impact of Sustainability Corporate Governance on Corporate Environmental Disclosure - Rizka Fitriasari (AIBPM Publisher, 2023)
The goal of this research is to assess the influence of Chief Sustainability Officers (CSOs) and Environmental Committees (ECs) on Corporate Environmental Disclosure (CED) in firms in Mineral and Coal Industry sector. This study, using purposive sampling, involved 75 sample companies of the said companies listed on the Indonesia Stock Exchange between 2015 and 2019. Based on the analysis, it was found that Chief Sustainability Officers (CSOs) and Environmental Committees (ECs) have no significant influence on Corporate Environmental Disclosure (CED). This research implies that companies can consider Corporate Environmental Disclosure necessary to show stakeholders their awareness of broader interests and accountability through behaving socially responsibly. This research’s samples were limited to corporations engaged in the Mineral and Coal Industry and registered in the Indonesia Stock Exchange. This empirical focused on the influence of Chief Sustainability Officers (CSOs) and Environmental Committees (ECs) on Corporate Environmental Disclosure (CED) in sustainability reports which are still rare among Indonesian business entities, especially those operating in Mineral and Coal Industry, using the control variables of Firm size, Leverage, and ROA.